Minocycline-Suppression of Early Peripheral Inflammation Reduces Hypoxia-Induced Neonatal Brain Injury - Min, Yingjun; Li, Hongchun; Xu, Kaiyu; Huang, Yilong; Xiao, Jie; Wang, Weizhou; Li, Longjun; Yang, Ting; Huang, Lixuan; Yang, Ling; Jiang, Hong; Wang, Qian; et al. (Frontiers in Neuroscience, 2017)
While extensive studies report that neonatal hypoxia-ischemia (HI) induces long-term cognitive impairment via inflammatory responses in the brain, little is known about the role of early peripheral inflammation response in HI injury. Here we used a neonatal hypoxia rodent model by subjecting postnatal day 0 (P0d) rat pups to systemic hypoxia (3.5h), a condition that is commonly seen in clinic neonates, Then, an initial dose of minocycline (45 mg/kg) was injected intraperitoneally (i.p.) 2h after the hypoxia exposure ended, followed by half dosage (22.5 mg/kg) minocycline treatment for next six consecutive days daily. Saline was injected as vehicle control. To examine how early peripheral inflammation responded to hypoxia and whether this peripheral inflammation response was associated to cognitive deficits. We found that neonatal hypoxia significantly increased leukocytes not only in blood, but also increased the monocytes in central nervous system (CNS), indicated by presence of C-C chemokine receptor type 2 (CCR2+)/CD11b+CD45+ positive cells and CCR2 protein expression level. The early onset of peripheral inflammation response was followed by a late onset of brain inflammation that was demonstrated by level of cytokine IL-1β and ionized calcium binding adapter molecule 1（Iba-1; activated microglial cell marker). Interrupted blood-brain barrier (BBB), hypomyelination and learning and memory deficits were seen after hypoxia. Interestingly, the cognitive function was highly correlated with hypoxia-induced leukocyte response. Notably, administration of minocycline even after the onset of hypoxia significantly suppressed leukocyte-mediated inflammation as well as brain inflammation, demonstrating neuroprotection in systemic hypoxia-induced brain damage. Our data provided new insights that systemic hypoxia induces cognitive dysfunction, which involves the leukocyte-mediated peripheral inflammation response.